2007
DOI: 10.3998/ark.5550190.0007.g18
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of stable phosphorus ylides from 3, 5-dimethylpyrazole and kinetic investigation of the reactions by UV spectrophotometry

Abstract: Stable crystalline phosphorus ylides were obtained in excellent yields from the 1:1:1 addition reactions between triphenylphosphine and dialkyl acetylenedicarboxylates, in the presence of a NH-acid, such as 3,5-dimethylpyrazole. These stable ylides exist in solution as a mixture of two geometrical isomers as a result of restricted rotation around the carbon-carbon partial double bond resulting from conjugation of the ylide moiety with the adjacent carbonyl group. To determine the kinetic parameters of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The prepared complexes are colourless (1, 4, 7), yellowish (2, 5, 8), or yellow (3,6,9) solids. The UV-vis spectra of 1-9 exhibit strong absorption bands below 300 nm [ε = (0.20-1.94) × 10 4 M −1 cm −1 ] that can be assigned to ligand-centred transitions of phosphine and/or isocyanide ligands [32]. The wide weak absorption bands in the 300-360 nm range with molar extinction coefficients [ε = (0.03-0.17) × 10 4 M −1 cm −1 ] can be assigned the d → d, π → π*, n → π* and changetransfer transition arising from π electron interactions between the metal and ligands, which involve either a metal-to-ligand or ligand-to-metal electron transfer [33,34].…”
Section: Synthesys and Charactrizationmentioning
confidence: 99%
“…The prepared complexes are colourless (1, 4, 7), yellowish (2, 5, 8), or yellow (3,6,9) solids. The UV-vis spectra of 1-9 exhibit strong absorption bands below 300 nm [ε = (0.20-1.94) × 10 4 M −1 cm −1 ] that can be assigned to ligand-centred transitions of phosphine and/or isocyanide ligands [32]. The wide weak absorption bands in the 300-360 nm range with molar extinction coefficients [ε = (0.03-0.17) × 10 4 M −1 cm −1 ] can be assigned the d → d, π → π*, n → π* and changetransfer transition arising from π electron interactions between the metal and ligands, which involve either a metal-to-ligand or ligand-to-metal electron transfer [33,34].…”
Section: Synthesys and Charactrizationmentioning
confidence: 99%
“…Often, it is sufficient to record continuously the absorbance of a reaction mixture in a thermostated cuvette at a fixed wavelength. The required instrumentation is www.prkm.co.uk readily accessible and numerous kinetic investigations of organic reactions have been reported using the UV-Vis technique [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The first catalytic reaction of arsonium ylides in 1989 reported that this property was vital in the synthesis of cyclopropanes with high diasteroselectivity [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A) Eyring plot (ln k obs /T versus 1/T) according to Eqn(9) for the reaction between DMAD, TPA and 1,3-dicarbonyl compounds in methanol. (B) A linearised form of the Eyring equation [Eqn(10), T ln k obs /T against T] for the reaction between DMAD, TPA and 1,3-dicarbonyl compounds in methanol.…”
mentioning
confidence: 99%